16S rRNA based microarray analysis of ten periodontal bacteria in patients with different forms of periodontitis. (October 2015) - Topcuoglu, Nursen; Kulekci, Guven
Abstract: DNA microarray analysis is a computer based technology, that a reverse capture, which targets 10 periodontal bacteria (ParoCheck) is available for rapid semi-quantitative determination. The aim of this three-year retrospective study was to display the microarray analysis results for the subgingival biofilm samples taken from patient cases diagnosed with different forms of periodontitis. A total of 84 patients with generalized aggressive periodontitis (GAP, n:29), generalized chronic periodontitis (GCP, n:25), peri-implantitis (PI, n:14), localized aggressive periodontitis (LAP, n:8) and refractory chronic periodontitis (RP, n:8) were consecutively selected from the archives of the Oral Microbiological Diagnostic Laboratory. The subgingival biofilm samples were analyzed by the microarray-based identification of 10 selected species. All the tested species were detected in the samples. The red complex bacteria were the most prevalent with very high levels in all groups. Fusobacterium nucleatum was detected in all samples at high levels. The green and blue complex bacteria were less prevalent compared with red and orange complex, except Aggregatibacter actinomycetemcomitas was detected in all LAP group. Positive correlations were found within all the red complex bacteria and between red and orange complex bacteria especially in GCP and GAP groups. Parocheck enables to monitoring of periodontal pathogens in all forms of periodontal disease and can be alternative to other guiding and reliable microbiologic tests. Highlights: Different forms of periodontitis were investigated by microarray technology. Red complex bacteria were the most prevalent in all forms of periodontitis. Positive correlations were found between red and orange complex bacteria. This technology can be alternative to other guiding and reliable microbiologic tests.